Pembeda Konsumen Dalam Memilih Tempat Belanja Offline Vs Online - Dede Suleman*; Hapzi Ali; Dewi Nusraningrum; Mochammad Mukti Ali (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
ABSTRACTThe new era of marketing adds an alternative shopping place for consumers where currently online shopping and offline shopping are present. So consumers must choose a shopping choice of the two alternatives. This makes the marketer need to map out what variables or factors from the demographic that make the consumer choose one of the available shopping places. This study looks at how consumers decide where to shop viewed from the consumer demographic factors. The population of this study is consumers of offline and online retail fashion products, of which the number is unknown, so the sample in this study uses non-probability of 130 respondents in DKI Jakarta. With SPSS analysis tools and discriminant analysis aids used, the results of this study indicate that the factors of education and employing consumers determine consumers to choose shopping at one shopping place. The key to successful marketers must focus on attracting the right consumers with the right way that is appropriate with the consumer's shopping behavior.Keywords: Consumer decisions, Demographics, Discriminant analysis